Building Sustainable Competitive Advantage: The Role of Social Capital and Innovation Capability in Women Entrepreneurship - Ramadani, Ramadani; Dalimunthe, Ritha F; Silalahi, Amlys Syahputra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the influence of social capital and innovation capability on competitive advantage in the context of women's entrepreneurship. Utilizing a quantitative approach with the PLS-SEM model, the study involved 300 respondents who are women entrepreneurs from various industry sectors. The findings indicate that social capital has a positive but insignificant effect on competitive advantage, while innovation capability has a strong and significant impact. These results highlight the importance of innovation as a key factor in creating sustainable competitive advantage, whereas social capital serves as an initial foundation for building business networks. Therefore, enhancing innovation capacity and access to technology should be prioritized in empowering women entrepreneurs to support the sustainability of their businesses in the future.